The In Vivo Anti-Tumor Effect of Curcumin Derivative (2E,6E)-2,6-bis(4-hydroxy-3-methoxybenzylidene) Cyclohexanone (BHMC) on 4T1 Breast Cancer Cells - Nursyamirah, Abd Razak; Akhtar, Muhammad Nadeem; Nadiah, Abu; Wan, Yong Ho; Sheau, Wei Tan; Seema, Zareen; Saiful Nizam, Tajuddin; Kamariah, Long; Noorjahan Banu, Alitheen; Swee, Keong Yeap (Royal Society of Chemistry, 2017)
Curcumin is one of the promising natural products extracted from the rhizomes of curcuma longa and has been extensively investigated by researchers to explore its potential as a chemopreventive and therapeutic agent against several chronic diseases. To further enhance the cytotoxic potential of curcumin, its derivative (2E,6E)-2,6-bis(4-hydroxy-3-methoxybenzylidene)cyclohexanone (BHMC) has been synthesized and investigated, and its antitumor effect on tested on 4T1 challenged mice. BHMC was recorded with in vitro cytotoxicity on murine 4T1 breast cancer cells with IC50 value 13.66 mM, which was 2 times lower than curcumin after 72 hours of treatment. An in vivo study indicated that BHMC possessed antitumor effect on the 4T1 cells of the challenged mice by induction of apoptosis, antiproliferation, antiinflammation and antimetastasis. This effect is better compared to curcumin treatment at the same evaluated concentration. Thus, BHMC is a potential antitumor agent against breast cancer.